THE RANGE OF ANTIBACTERIAL MEDICINAL PRODUCTS PRESENTED ON THE PHARMACEUTICAL MARKET OF UKRAINE - Паламар, Аліна; Круглик, Яна (SWorldJournal, 2025)
The article presents an analysis of the Ukrainian pharmaceutical market of antibacterial drugs belonging to ATC group «J01 – Antibacterials for systemic use». The study includes an analysis of the range of active pharmaceutical ingredients and dosage form